Influence of frozen storage period on the biochemical, nutritional, and microbial quality of Skipjack tuna (Katsuwonus pelamis) collected from the Bay of Bengal coast of Bangladesh. (October 2022) - Chakma, Suprakash; Rahman, Md. Arifur; Mali, Sujan Kanti; Debnath, Sourav; Hoque, Md. Sazedul; Siddik, Muhammad A.B.
Highlights: Nutritional composition of Skipjack tuna ( Katsuwonus pelamis ) fillet was compared under frozen (-18°C) storage conditions at various storage periods (15, 30, and 60 days). Tuna fillet is an excellent source of glutamic acid, histidine, leucine, aspartic acid, and lysine. Histamine content was less than 50 mg/kg from fresh to frozen storage demonstrates no prone to allergic reaction. Dietary lipid in fresh tuna fillet was significantly better than that of 60 days storage period. Fresh to 60 days frozen storage tuna fillet, ∑EPA + DHA (%) was higher than the recommended dietary reference values set by the EFSA. The entire experiment showed the bacterial loads within permeable limits set by ICMSF. Finally, frozen storage of tuna fillets up to 60 days had no negative effects on their nutritional quality. Abstract: The biochemical and microbial quality of skipjack tuna ( Katsuwonus pelamis ) fillets were investigated at various storage periods (15d, 30d and 60d) under frozen (-18°C) storage conditions. In the present study, the biochemical components of frozen tuna fillets were found to be significantly different for the entire storage period (p<0.05). Furthermore, the histamine content was less than 50mg/kg from fresh to frozen storage. All the amino acids were significantly different (p<0.05) with the presence of high amounts of glutamic acid (11.11 to 11.22g/100g), histidine (8.42 to 8.97g/100g), leucine (7.44 to 7.50g/100g), aspartic acid (7.28 to 7.37g/100g), and lysine (6.22 to 6.29g/100g). Among the twelve fatty acids, docosahexaenoic acid (C22:6, DHA), oleic acid (C18:1), and palmitic acids were the most abundant. The lipid indices showed that tuna muscle is a potential source of ω-3 and ω-6 fatty acids. All the parameters used for determining the bacterial loads were within permeable limits set by ICMSF under frozen storage conditions. Finally, storing tuna fish fillets for up to 60 days exhibited no detrimental nutritional consequences and the safe for consumption.